Cultivation of Different Oyster Mushroom (Pleurotus species) on Coffee Waste and Determination of Their Relative Biological Efficiency and Pectinase Enzyme Production, Ethiopia - Dissasa, Guta (International Journal of Microbiology, 2022)
Cultivation of specialty mushrooms on lignocellulosic wastes represents one of the most economic and cost-effective organic recycling processes. Solid-state cultivation (SSC) was carried out to evaluate the feasibility of using coffee waste (husk and parchment) as substrate for cultivation of oyster mushroom (Pleurotus species). The periods for spawn running, pinhead and fruit body formation, number of flushes, yield, and biological efficiency of the four Pleurotus species (P. citrinopileatus, P. eryngii, P. ostreatus, and P. sapidus) grown on coffee husk and parchment were studied. The results revealed that the time for the first appearance of pinhead was shortest for P. ostreatus (20–21) days followed by P. sapidus (22–23) days on coffee husks, while P. eryngii and P. citrinopileatus required 26–27 days and 23–24 days, respectively, on the some substrate. All the four Pleurotus species recorded at least four flushes and three flushes on coffee husk and parchment, respectively; flush 1 gave the highest yield while flush 3 and 4 gave the lowest yield. The biological efficiency (B.E.) for P. citrinopileatus, P. eryngii, P. ostreatus and P. sapidus obtained from fresh coffee husk was 26.54, 40.94, 60.33, and 55.72, respectively. Significant differences (P<0.05) in yield and % B.E. of the four mushrooms species were recorded. The results also showed that the B.E. (61.92%) of P. ostreatus grown on composted coffee husk was insignificantly higher (P<0.05) than that grown on noncomposted coffee husk (60.33). The yields of P. sapidus obtained from the two substrates were almost comparable with that of P. ostreatus. There was a significant difference at (P<0.05) observed between noncomposted and composted coffee husk and coffee parchment as well as between coffee husk and coffee parchment on yield and biological efficiency (B.E.). Composted coffee waste is more efficient than noncomposted one. Pectinase enzymes productions by these mushrooms were also studied. They are known to produce extracellular enzymes, particularly pectinase, which contribute to the biochemical decomposition of pectin-rich lignocellulosic wastes biomass. Accordingly, P. sapidus showed more pectolytic activities followed by P. ostreatus. But the pectolytic activity showed by P. eryngii and P. citrinopileatus was relatively lower. The implications of this study are the feasibility of using composted coffee husks and coffee parchment with the supplementary substrate to cultivate very protein-rich mushrooms for food in solid-state cultivation (SSC) while at the same time promoting environmental sustainability.